«Variations on “I got rhythm”» by George Gershwin: concert transformation of the song theme - Antonova, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
Relevance of the study. George Gershwin's concert legacy includes four works for piano and orchestra: Rhapsody in Blue, Concerto in F, Second Rhapsody, Variations on “I Got Rhythm”. However, the degree of their popularity, performance demand and scholarly coverage are disproportionate, with the Variations on “I Got Rhythm” being the most overlooked in this regard, which seems unfair considering their final role in the composer's instrumental creativity. The appeal to the Variations is also made more relevant by the clear combination in them of two spheres of Gershwin's activity — popular music and academic music. The main objective of the study is to examine George Gershwin's Variations on “I Got Rhythm” for piano and orchestra in the unity of figurative, stylistic and genre parameters and to prove that the work meets the requirements of the concert genre. The scientific novelty is determined by the fact that Variations on “I Got Rhythm”, encapsulating Gershwin's exploration of instrumental music, are studied for the first time in Ukrainian musicology. The methodology of the article is based on historical, cultural, genre-stylistic, intonation-dramaturgical methods of analysis. The results and conclusions. Variations on “I Got Rhythm” for piano and orchestra by George Gershwin, his last instrumental work and the summation of his search in the piano concerto genre, is considered. The circumstances of the creation and premiere performances of the Variations are highlighted. The connections of the figurative concept of the work with the national American idea and the reflection of the signs of American modernity in Gershwin's imagination directly in the music of the work are revealed. The combination of two spheres of Gershwin's activity — popular music (the theme of his own song as an object of variation) and academic music (traditions of characteristic Romantic variations and rationalistic techniques of modernist writing) — in the Variations on “I Got Rhythm” is emphasized. It is noted that Gershwin's skills of virtuoso variation of musical themes were honed in his encore concert performances and playing music at parties, and the experience of writing down such improvisations in writing was acquired while working on the Song-book for Piano. The Variations on "I Got Rhythm" are analysed in detail. The degree and methods of transformation of the theme, derivation of melodic voices, passages, figurations, counterpoint lines from the title motif are traced; the means contributing to the external completeness of the variation cycle and the symmetry of its internal organisation are considered. The embodiment of the attributive features of an instrumental concert in Gershwin's Variations is characterized: dialogicity, revealed in the interaction of orchestral and piano parts; soloing, represented by textural models borrowed from classical and jazz pianism; the game, which manifesting itself in the forms of competition, mystification, mosaic, joke, mastery of playing an instrument. The study emphasizes the dominance of the playful principle in Gershwin's Variation, which is due to Gershwin's creative method, formed in his work on Broadway, and reflects the traits of his personality.